2011
DOI: 10.4103/0974-777x.77289
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus Aureus: Prevalence and current susceptibility pattern in Sikkim

Abstract: Background:Prevalence of methicillin-resistant Staphylococcus Aureus (MRSA) strains is reported to be increasing globally.Objectives:The study was conducted to find the magnitude and antibiotic susceptibility pattern of MRSA infection in a referral tertiary care teaching hospital of Sikkim, India.Materials and Methods:In this cross sectional study, 827 clinical specimens were collected from different departments of Central Referral Hospital. One hundred and ninety-six carrier screening nasal swabs were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The higher frequency of S. aureus isolation in pus samples compared to blood samples has been reported in other studies in the region and elsewhere [22, 29, 30]. Other investigators have however reported the converse [31]. The observed variation in proportion of S .…”
Section: Discussionmentioning
confidence: 50%
“…The higher frequency of S. aureus isolation in pus samples compared to blood samples has been reported in other studies in the region and elsewhere [22, 29, 30]. Other investigators have however reported the converse [31]. The observed variation in proportion of S .…”
Section: Discussionmentioning
confidence: 50%
“…[91011121314151617181920] Multi-resistant enterobacteriaceae due to the production of extended spectrum β-lactamases (ESBL) have become very common in India. [1112] In addition, various studies in South India highlighted the drug resistance pattern like multidrug resistant Extended-Spectrum β-Lactamase Producing Klebsiella pneumoniae , Ciprofloxacin resistant Salmonella enteric serovar Typhi , emergence of vancomycin-intermediate staphylococci , fluoroquinolone resistance among Salmonella enteric serovar Paratyphi A, Pseudomonas aeruginosa and Acinetobacter baumannii resistant to ceftazidime, cefepime and ciprofloxacin.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in Sikkim, India found that MRSA was seen in 111out of 291 clinical specimens (38.14%) of S. aureus and 41out of 196 carrier screening nasal samples (20.92%) of S. aureus and overall a total of 152 isolates of S. aureus from 487 specimens (31.21%) were found to be methicillin resistant. [20] Result of 88 references showed a steady increase in the number of vancomycin-intermediate and vancomycin-resistant S. aureus in hospitalized patients with highlighting the spread of MRSA from the hospital to the community. [24] Another study showed increased rate of inducible clindamycin resistance among CA-MRSA.…”
Section: Methodsmentioning
confidence: 99%
“…High rates of Methicillin-Resistant Staphylococcus aureus (MRSA) in clinical samples have been noted in one study from North East India. [ 5 ] Similarly, resistance to the glycopeptide antibiotics such as vancomycin and tiecoplanin among clinical isolates of enterococci is also increasing. [ 6 ] Empirical treatment of infection in the cancer patient is often arbitrarily attempted by administration of broad spectrum or combination antibiotics until culture, and susceptibility results are available.…”
Section: Introductionmentioning
confidence: 99%